The effects of extraction of pulpally involved primary teeth on weight, height and BMI in underweight Filipino children. A cluster randomized clinical trial - Monse Bella; Duijster Denise; Sheiham Aubrey; Grijalva-Eternod Carlos S; van Palenstein Helderman Wim; Hobdell Martin H (BMC, 2012)
Abstract Background Severe dental caries and the treatment thereof are reported to affect growth and well-being of young children. The objective of this study was to assess the effects of extraction of severely decayed pulpally involved primary teeth on weight and height in underweight preschool Filipino children. Methods Underweight preschool Filipino children with severe dental decay had their pulpally involved primary teeth extracted during a stepped wedge cluster randomized clinical trial. Day care centers were randomly divided into two groups; children from Group A day care centers received treatment as soon as practical, whereas children from Group B day care centers were treated four months after Group A. Clinical oral examinations using WHO criteria and the pufa-index were carried out. Anthropometric measurements were done on both groups immediately before treatment of Group A and at follow-up four months later. Height and weight z-scores were calculated using 2006 and 2007 WHO Growth Standards. Multilevel analysis was used to assess the effect of dental extractions on changes in anthropometric measurements after dental treatment. Results Data on 164 children (85 in Group A and 79 in Group B), mean age 59.9 months, were analyzed. Both groups gained weight and height during the trial period. Children in Group A significantly increased their BMI (p < 0.001), and their weight-for-age (p < 0.01) and BMI-for-age z-scores (p < 0.001) after dental treatment, whereas untreated children in Group B did not. Children in Group A had significantly more weight gain (p < 0.01) compared to untreated children in Group B. However, children in Group A had an inverse change in height gain (p < 0.001). Adjustment for the time interval between the two visits had little effect on the results. Conclusions The extraction of severely decayed primary teeth resulted in significant weight gain in underweight Filipino children. Untreated dental decay should be considered an important co-factor affecting child growth and should be considered when planning for interventions to improve child growth. Trial registration ISRCTN90779069 http://www.controlled-trials.com/isrctn/isrctn_loa